2003
DOI: 10.1093/annonc/mdg455
|View full text |Cite
|
Sign up to set email alerts
|

Oral vinorelbine in combination with cisplatin: a novel active regimen in advanced non-small-cell lung cancer

Abstract: The efficacy and safety of the alternating vinorelbine schedule (i.v. on day 1, oral on days 8, 15 and 22) in combination with cisplatin in advanced NSCLC are similar to those of the standard regimen using exclusively i.v. vinorelbine, whereas ease of administration and patient comfort may favor the novel approach.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
21
0
2

Year Published

2004
2004
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(26 citation statements)
references
References 16 publications
3
21
0
2
Order By: Relevance
“…Although the combination of oral VNB and cisplatin has been tested in NSCLC [12,13] there is a complete lack of experience concerning the combination of metronomic administration of vinorelbine with standard iv administration of cytotoxic drugs. Other platinum-based metronomic chemotherapy regimens have shown significant efficacy and a very favorable toxicity profile, even in NSCLC patients with poor prognosis [14].…”
Section: Introductionmentioning
confidence: 99%
“…Although the combination of oral VNB and cisplatin has been tested in NSCLC [12,13] there is a complete lack of experience concerning the combination of metronomic administration of vinorelbine with standard iv administration of cytotoxic drugs. Other platinum-based metronomic chemotherapy regimens have shown significant efficacy and a very favorable toxicity profile, even in NSCLC patients with poor prognosis [14].…”
Section: Introductionmentioning
confidence: 99%
“…Oral chemotherapy is preferred by patients over intravenously administered treatment [33]. When used as a single agent, oral vinorelbine demonstrated a comparable efficacy and safety as intravenous form in advanced NSCLC [34]. Results on alternating intravenous and oral vinorelbine in combination with cisplatin were also reported by the same group who demonstrated similar efficacy as the intravenous form [34].…”
Section: Discussionmentioning
confidence: 99%
“…In patients with NSCLC, oral and intravenous Vinorelbine have been shown to have comparable activity. 115 In pharmacokinetic studies, equivalence in bioavailability has been demonstrated between the oral and intravenous formulation. 116 Oral Vinorelbine is rapidly absorbed, with a T max of 0.75-1.4 hours.…”
Section: Oral Vinorelbinementioning
confidence: 99%